Interaction analysis of hemolymph extracellular vesicles miRNA and hemocytes mRNA reveals genes and pathways associated with molting in Scylla paramamosain - Qiao, Ying; Ma, Xiaowan; Huang, Lixing; Zhong, Shengping; Xing, Yongze; Chen, Xuyang (Frontiers in Marine Science, 2022)
Molting is a key biological process in crustaceans, with impacts on their growth, development and reproduction. Extracellular vesicles (EVs) serve as bio-cargo carrying such as nucleic acids, proteins, and lipids which mediate intercellular communication and participate in various cell biological processes. In this study, we obtained hemocyte transcriptome data during the intermolt, premolt, and postmolt stages of the mud crab Scylla paramamosain. We analyzed the differentially expressed genes in the three stages of molt and identified a number of immune-related genes and structural cuticle genes. We then isolated and characterized the EVs from the hemolymph of S. paramamosain and sequenced their miRNA. In total, we characterized 89 EVs microRNAs (miRNAs) targeting 1447 genes that are potentially involved in the molting process of S. paramamosain. The EVs miRNAs mainly regulated the immune-related genes and affected the molting process by mediating ecdysone signaling and insulin signaling pathways during the mud crab molt cycle. This is the first study of EVs miRNAs and their interaction with mRNA to identify important candidate genes associated with, or regulating, the molting process. This study provides a better understanding of, and novel insights into, the molting cycle of crustaceans and offers baseline information for further studies in the mechanisms regulating molt.